China, Taiwan, and the Battle for Latin America - Erikson, Daniel P.; Chen, Janice (Tufts Archival Research Center, 2005)
Volume 31, Issue 2. Summer Latin America is the latest battleground in China and Taiwan's struggle for international legitimacy. If Washington does not play a much-needed role in advising the burgeoning democracies and economies in its own backyard, Latin American states may fall victim to East Asia's competing interests.